Short-term hypertension management in community is associated with long-term risk of stroke and total death in China: A community controlled trial. Issue 48 (November 2016) - Wang, Zengwu; Hao, Guang; Wang, Xin; Wang, Wen; Chen, Weiwei; Zhu, Manlu
Abstract : Supplemental Digital Content is available in the text Abstract: Background: It is not fully clear whether the effect of short-term management in community can reduce the long-term risk of stroke Objectives: To evaluate whether short-term hypertension management is associated with long-term incidence of stroke and total death in community health centers in China. Design: Community controlled trail. Participants: Six community health centers (4 active, 2 control) in China, patients with hypertension. Control arm: Patients were treated with normally therapy method. Active arm: Patients were treated oriented by the Guideline for hypertension management. Randomization: Two centers (Hebei and Zhejiang) from the Hypertension Control in Community (HCC) Project, which was conducted from 2005 to 2008, were randomly selected for this study. Four thousand hypertensive patients from these centers, who were under management for one year in the baseline, were followed up in 2013. The electronic health record system (2005–2008) was used to identify 2000 hypertensive patients, who were not included in HCC but lived in comparable community health center in the same province, as the control group. All baseline and follow-up data were collected using standardized questionnaires for stroke outcomes. Main outcome measures: Stroke. Results: Of the 6000 participants, 3787 (63.1%) were eligible for analysis. At the time of follow-up, the average BP was kept in the lower level than that in baseline, and the control rate was 59.3%. After propensity-score matching, 110 strokes (2.0% vs 4.6%) and 141 deaths (1.4% vs 3.8%) were noted in the matched intervention and control groups (1078 pairs), respectively. Patients in the intervention group were less likely to experience a stroke or die than those in the control group (hazard ratio [HR] = 0.40, 95% confidence interval [CI]: 0.26–0.62, P < 0.01; HR = 0.50, 95% CI: 0.35–0.72, P < 0.01). The sensitivity analysis showed similar results. Conclusions: Short-term management of hypertension had a positive effect on the long-term risk reduction of death and stroke in hypertensive patients.